“OPTIMISING LAW ENFORCEMENT: ADVANCING PUBLIC SAFETY WITH THE POLICE COMMISSIONERATE SYSTEM” (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a critical analysis of the Police Commissionerate System as aninstrumental approach to achieving effective policing in contemporary law enforcement. ThePolice Commissionerate System, characterized by centralized command and control underthe leadership of a Police Commissioner, has gained prominence as a mechanism to enhanceefficiency, responsiveness, and accountability within police organizations.